2018
DOI: 10.1186/s41937-018-0021-3
|View full text |Cite
|
Sign up to set email alerts
|

Openness and productivity of the Swiss economy

Abstract: This paper analyzes the connection between openness and economic performance in Switzerland. Considering different dimensions of openness, we show that the Swiss economy is classified as relatively open. Nevertheless, there still is potential to further increase international integration, particularly through deregulation in the services sector. We also show that for some branches in the Swiss manufacturing sector, increases in international trade are associated with higher productivity in the long run. With r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Greater trade openness may positively influence economic complexity by supporting the diffusion of knowledge and transfer of technology through imported goods and services (of which the intermediate goods) at lower costs (e.g., Coe & Helpman, 1995;Grossman & Helpman, 1991;Grossman & Helpman, 2015;Navas, 2015). Moreover, through its positive impact on total factor productivity (e.g., Föllmi et al, 2018;Hübler & Pothen, 2017;Melitz 2003;Miller & Upadhyay, 2000), trade openness can induce greater economic sophistication. Sepehrdoust et al (2019) reported that trade policy liberalization is conducive to greater economic complexity.…”
Section: A Model Specificationmentioning
confidence: 99%
“…Greater trade openness may positively influence economic complexity by supporting the diffusion of knowledge and transfer of technology through imported goods and services (of which the intermediate goods) at lower costs (e.g., Coe & Helpman, 1995;Grossman & Helpman, 1991;Grossman & Helpman, 2015;Navas, 2015). Moreover, through its positive impact on total factor productivity (e.g., Föllmi et al, 2018;Hübler & Pothen, 2017;Melitz 2003;Miller & Upadhyay, 2000), trade openness can induce greater economic sophistication. Sepehrdoust et al (2019) reported that trade policy liberalization is conducive to greater economic complexity.…”
Section: A Model Specificationmentioning
confidence: 99%
“…For some, trade openness improves tax revenues through the productivity channel (Edwards 1998;Melitz 2003;Föllmi et al 2018). Lotz and Morss (1970) also supported the positive effect of trade openness by the fact that tax administration has the ease of taxing imports and exports.…”
Section: Methodsmentioning
confidence: 85%
“…In addition, other variables such as foreign development aid cause and governance are endogenous in the tax ratio equation. Indeed, through the thesis of the Samaritan's dilemma, Gibson et al (2005) show that foreign development aid recipient countries can strategically maintain poor fiscal performance to continue to receive higher concessional aid indefinitely. In this context, a low tax effort causes foreign development aid inflows.…”
Section: Methodsmentioning
confidence: 99%
“…Greater trade openness is expected to in uence positively economic complexity by supporting the diffusion of knowledge and transfer of technology, including through the imported goods and services (of which the intermediate goods) at lower costs (e.g., Coe and Helpman 1995;Grossman and Helpman, 1991;Grossman and Helpman 2015;Navas, 2015). Moreover, by through its positive impact on total factor productivity (e.g., Föllmi et al, 2018;Hübler and Pothen, 2017;Melitz 2003;Miller and Upadhyay, 2000), trade openness can induce greater economic sophistication. Sepehrdoust et al (2019) have reported that trade policy liberalization is conducive to greater economic complexity.…”
Section: Model Speci Cationmentioning
confidence: 99%